Little known ophthalmic interests of Emil von Behring, the first Nobel Prize Laureate in Medicine or Physiology. (15th February 2012) - Grzybowski, Andrzej; Wilhelm, Helmut
Abstract: Although the work for which Emil von Behring (1854–1917) was awarded the first Nobel Prize Winner for Medicine or Physiology in 1901 was on serum therapy, not only was he trained and worked as an ophthalmologist but he also wrote his doctoral dissertation on a practical ophthalmological topic whilst in Berlin under Carl Schweigger (1830–1905). He later worked for 3 years as an assistant and co‐worker with the famous Polish ophthalmologist Boleslaw Wicherkiewicz (1847–1915), in Poznan where he described an interesting ophthalmic case in a scientific journal. His life and work in other fields have been well studied, but his interests and relationship to ophthalmology that played an important role in, at least part of, Behring's life have never previously been analysed thoroughly.